Diversidade alélica do gene DRB3 do complexo principal de histocompatibilidade nas raças de búfalo mediterrâneo, Jafarabadi e Murrah - Olivatto, Lucas Matheus [UNESP] (2013)
The Major Histocompatibility Complex (MHC) is a genome region with have a dense clusters of genes that showing a high degree of polymorphism. The genes of the MHC are divided in regions that show similar functions, and contain genes of the classe I, II and III. The class II, in bovides is subdivided in two clusters called IIa and IIb. Much attention has been given to class II genes, especially to the livestock, because the production animal has a need of more efficient methods to control diseases through the development of vaccines and selection of resistant animals. Therefore, the present work aimed study the allelic diversity of the DRB3 gene in three breeds of river buffaloes raised in Brazil (Mediterranean, Jafarabadi and Murrah) by PCR-RFLP. DNA samples were extracted from follicle bulb of 24 Mediterranean, 23 Jafarabadi and 18 Murrah buffaloes breeds. The PCR reactions have 30 μl of volume and the PCR product was digested with three restriction enzymes: RsaI, HaeIII and PstI. The primers pairs produced a PCR product with 300 bp size proximally. Digestion with the restriction enzyme RsaI presented eight alleles, with proximally sizes: O (300 bp), RsaI-A (230+70 bp), RsaI-B (180+120 bp), RsaI-C (130+90+70 bp), RsaI-D (140+90+70 bp), RsaI-E (120+70+60 bp), RsaI-F (120+110+70 bp) and RsaI-G (110+70+60+55 bp), and were five alleles (O, RsaI-A, RsaI-B, RsaI-C and RsaI-E) in the Mediterranean breed, four alleles (O, RsaI-A, RsaI-F and RsaI-G) in the Jafarabadi breed and three alleles (O, RsaIA and RsaI-D) in the Murrah breed. In all of the PCR products, of the three breeds, the homozygote genotype for the allele O was the most frequent (300bp/300bp). Digestion with the HaeIII restriction enzyme produced four alleles, with proximally sizes: HaeIII-A (220+80 bp), HaeIII-B (170+80+50 bp), HaeIII-C (210+80 bp) and HaeIII-D (170+130 bp), where the Mediterranean breed presented the four alleles ...